Heroes, monsters, and ideal victims: a narrative approach in understanding online child sexual exploitation investigators’ perceptions of perpetrators and victims - Brewer, Christopher Glenn (Kansas State University, 2023)
The development of information communication technologies (ICTs) has led to a growth of the production and consumption of child sexual exploitation materials (CSEM). The enforcement of these crimes has largely fallen upon policing agencies and specialized units dedicated to investigating internet-facilitated crimes against children. Unfortunately, little research has been conducted on individual cybercrime units despite their importance and notable imperative in combatting child exploitation. Specifically, there has been no examination on how ICAC investigators understand their fellow investigators, CSEM perpetrators, or victims of child exploitation. With the help of narrative criminology, this research explored how stories and storytelling help us better understand (1) ICAC investigators’ sense of occupational identity, (2) their understanding of offenders, and (3) their understanding of victims. Analysis revealed three core narratives from the stories of these investigators: (1) the “Misunderstood Hero,” (2) the “Incorrigible Menace,” and (3) the “Ideal Victim.” To answer these questions, this study analyzed a dataset of 47 qualitative interviews with ICAC detectives, civilian analysts, and administrators gathered as part of a National Science Foundation (NSF)-funded study on cybercrime policing (Award # 1916284). A narrative criminological approach best informed the analytical development of perceptions through the power of language and storytelling.
Keywords: Cybercrime; Narrative criminology; Monsters; Police culture; Internet crimes against children